Comprehensive Quality Standards in the Jordanian Soccer Association from the Perspective of the Boards of Directors of Professional Soccer Clubs (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study aimed to identify the comprehensive quality standards in the Jordanian Soccer Association from the perspective of the boards of directors of professional soccer clubs, and to identify the differences that pertain to the variables of educational level and years of experience. The descriptive approach was used, and the study sample consisted of (90) intentionally selected members. The questionnaire that was used as a data collection tool consisted of (34) items that covered four domains: quality planning, infrastructure, administrative strategies, and professional competencies. Arithmetic means, standard deviations, percentages, correlation coefficient and analysis of variance were used. The results of the study showed that the comprehensive quality standards in the Jordanian Soccer Association, from the perspective of the boards of directors of professional Soccer clubs, came at an average level. The topic of ‘infrastructure’ came in the first place; that of administrative strategies came in the second place; the quality planning came in the third place, and the professional competencies ranked fourth and last. The study also showed, in light of the results, that there were no differences attributed to the study variables (educational level, years of experience). The researchers recommend that members of the Federation’s Board of Directors develop the necessary plans and strategies in order to develop comprehensive quality standards in the Jordanian Soccer Association, to emphasize the need to develop the performance level of employees and to transfer experience through seminars and courses, and to increase financial support for developing the infrastructure as it is in constant need of development
Keywords: Comprehensive Quality; Standards; Unions; Soccer